Cotton tolerance to halauxifen-methyl applied preplant. (August 2019) - Askew, M. Carter; Cahoon, Charles W.; York, Alan C.; Flessner, Michael L.; Langston, David B.; Ferebee, J. Harrison
Abstract: Auxin herbicides are used in combinations to control glyphosate-resistant horseweed preplant burndown. Herbicide labels for 2, 4-D–containing products require a 30-d rotation interval for planting cotton cultivars not resistant to 2, 4-D. Dicamba labels require an accumulation of 2.5 cm of rain plus 21 d per 280 g ae ha –1 rotation interval for planting cotton cultivars not resistant to dicamba. Previous research has shown that cotton injury caused by dicamba applied 14 d before planting was transient with little effect on cotton yield, whereas 2, 4-D has little effect on cotton when applied 7 d prior to planting. Injury caused by dicamba and 2, 4-D is inversely related to rainfall received between herbicide application and cotton planting. Experiments were conducted to evaluate cotton tolerance to halauxifen-methyl, a new Group 4 herbicide, applied at intervals shorter than labeled requirements. Experiments were established near Painter and Suffolk, VA, and Belvidere, Clayton, Eure, Lewiston, and Rocky Mount, NC, during the 2017 and 2018 growing seasons. Herbicide treatments included halauxifen, dicamba, and 2, 4-D applied 4, 3, 2, 1, and 0 wk before planting (WBP). Visible estimates of cotton growth reduction and total injury were collected 1, 2, and 4 wk after cotton emergence (WAE). Cotton stand and percentage of plants with distorted leaves were recorded 2 and 4 WAE. Cotton plant heights were recorded 4 and 8 WAE. Halauxifen was less injurious (9%) than dicamba (26%) or 2, 4-D (21%) 2 WAE when herbicides were applied 0 WBP. Cotton stand reduction 2 WAE by halauxifen was less than 2, 4-D and dicamba when applied 0 WBP. Injury observed from herbicides applied 1, 2, 3, and 4 WBP was minor, and no significant differences in cotton stand were observed. Early-season cotton injury was transient, and seed cotton yield was unaffected by any treatment.